On the Green Function of the Annulus (Analysis in Theory and Applications, 2016)
Using the Gegenbauer polynomials and the zonal harmonics functions we give some representation formulae of the Green function in the annulus. We apply this result to prove some uniqueness results for some nonlinear elliptic problems.